The effect of core stability and functional exercises on selected speed and strength parameters in expert female footballers - Niewolna, N.; Zwierko, T. (Central European Journal of Sport Sciences and Medicine, 2015)
Designed to strengthen the deep (stabilizer) muscles which stabilize joints and ligaments, core stability exercises are important for the development of motor skills in athletes. In this research, we aimed to determine how a two-year program of core stability and functional exercises influenced the strength and speed of female football players. The tested athletes (n = 17) were members of Olimpia Szczecin MKS, a first division football club from Poland. Their mean age was 19.8 ±1.4 years, while the mean duration of sport experience was 6 years. We analyzed their running speed, as well as the maximal strength of eight major muscle groups: rectus abdominals, abdominal oblique, shoulder girdle, chest, upper limbs, quadriceps, biceps and gastronomies. The effects of training on motor speed and strength were measured twice, prior to each of the two seasons. The functional training resulted in significant changes in the strength of various muscle groups: quadriceps (d17.1 kg; p < 0.05), abdominal oblique muscle (d9.1 kg; p < 0.05), shoulder girdle (d3.6 kg; p < 0.05) and chest (d3.5 kg; p < 0.05). There was also a significant reduction in the time of the 30 meter sprint (p < 0.05) (d0.1 s; p < 0.05). In summary, functional training had a positive effect on the strength and running speed of the tested female footballers.